Cognitive impairment with diabetes mellitus and metabolic disease: innovative insights with the mechanistic target of rapamycin and circadian clock gene pathways. Issue 1 (2nd January 2020) - Maiese, Kenneth
ABSTRACT: Introduction : Dementia is the 7th leading cause of death that imposes a significant financial and service burden on the global population. Presently, only symptomatic care exists for cognitive loss, such as Alzheimer's disease. Areas covered : Given the advancing age of the global population, it becomes imperative to develop innovative therapeutic strategies for cognitive loss. New studies provide insight to the association of cognitive loss with metabolic disorders, such as diabetes mellitus. Expert opinion : Diabetes mellitus is increasing in incidence throughout the world and affects 350 million individuals. Treatment strategies identifying novel pathways that oversee metabolic and neurodegenerative disorders offer exciting prospects to treat dementia. The mechanistic target of rapamycin (mTOR) and circadian clock gene pathways that include AMP activated protein kinase (AMPK), Wnt1 inducible signaling pathway protein 1 (WISP1), erythropoietin (EPO), and silent mating type information regulation 2 homolog 1 (Saccharomyces cerevisiae ) (SIRT1) provide novel strategies to treat cognitive loss that has its basis in metabolic cellular dysfunction. However, these pathways are complex and require precise regulation to maximize treatment efficacy and minimize any potential clinical disability. Further investigations hold great promise to treat both the onset and progression of cognitive loss that is associated with metabolic disease.